已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 20:36:36
已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2
已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y
已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y
已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y
(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y
=(x+y)(x-y)-y^2+(x-y)^2-2y(3x^2-xy)÷2y
=(x+y)(x-y)-y^2+(x-y)^2-(3x^2-xy)
=(x+y)(x-y)+(x-y)^2-y^2-(3x^2-xy)
=[(x+y)+(x-y)](x-y)-y^2-(3x^2-xy)
=2x(x-y)-y^2-(3x^2-xy)
=2x^2-2xy-y^2-3x^2+xy
=-x^2-xy-y^2
=-(x^2+y^2+xy)
=-(x^2-2xy+y^2+3xy)
=-[(x-y)^2+3xy]
=-[3^2+3*(-2)]
=-(9-6)
=-3
(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y
=x²-y²-y²+x²+y²-2xy-3x²+2xy
=-x²-y²+2xy-2xy
=-[(x-y)²+2xy]
=-[9-4】
=-5
x=-1,y=2,代入可得3
已知X+Y=3XY,求2X+2Y-XY除以X+Y+2XY的值,要算理.已知X+Y=3XY,求2X+2Y-XY除以X+Y+2XY的值,要算理.
已知:x/y=-2,求x^2-2xy-3y^2/x^-6xy
已知xy=-2,x-y=3,求(x+y)(x-y)-y^2+(x-y)^2-(6x^2y-2xy^2)÷2y
已知xy/x+y=3,求2x-3xy+2y/-x+3xy-y的值
已知xy/x+y=3,求2x-3xy+2y/-x+3xy-y的值
已知x-y=3xy,求分式3x+2xy-3y/x-2xy-y的值
已知y=3xy+x,求代数式2x+3xy-2y/x-2xy-y的值
已知x-y/xy=3,求分式2x+3xy-2y/x-2xy-y的值.
已知3/(x-y)=1/xy 求(-x-2xy+y)/ (2x+3xy-2y)
已知x-y=3xy,求2x+3xy-2y/x-2xy-y
已知x-y=3xy,求2x-3xy-2y/x-2xy-y
已知y=3xy+x,求代数式2x+3xy-2y/x-2xy-y的值
已知xy/x+y=3,求代数式2x-5xy+2y/x-3xy+y
已知3x=xy+3y,求2x+xy-2y/y-x-xy的值
已知xy/x+y=2,求代数式3x-5xy+3y/-x+2xy-y的值
已知xy/x+y=2,求代数式3x-xy+3y/-x+3xy-y的值
已知xy/x+y=6,求3x-2xy+3y/-x+3xy-y的值.
已知(xy)/(x+y)=6求(3x-2xy+3y)/(-x+3xy-y)的值.